Unstable os odontoideum contributing to cervical myelopathy and obstructive sleep apnea - Rahimizadeh, Abolfazl (Surg Neurol Int, 2019)
BACKGROUND: Sleep apnea is characterized by repetitive cessation of breathing during sleep. It may be attributed to obstructive, central, or mixed pathologies close to the upper airway resulting in a decreased diameter of the oropharyngeal tract. CASE DESCRIPTION: A 36-year-old male with progressive cervicomedullary myelopathy/quadriparesis exhibited obstructive sleep apnea (OSA) attributed to an anteriorly displaced os odontoideum (OO). Atlantoaxial screw-rod stabilization resulted in improvement of both neurological function and OSA. CONCLUSION: A symptomatic unstable OO may contribute to suboccipital pain, progressive quadriparesis, vertebrobasilar insufficiency, and OSA. Appropriate operative intervention utilizing atlantoaxial screw-rod stabilization may help to resolve these deficits.